2014
DOI: 10.1097/brs.0000000000000039
|View full text |Cite
|
Sign up to set email alerts
|

Femoral Nerve Strain at L4–L5 Is Minimized by Hip Flexion and Increased by Table Break When Performing Lateral Interbody Fusion

Abstract: N/A.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…These results show that when considering the trans-psoas and oblique approaches, sitting MRIs may dissuade surgeons from attempting an LLIF in specific patients. Flexion of the hips to 45–60 degrees intraoperatively has been advocated by O'Brien et al [ 16 ] in which they reported it would reduce strain in the lumbar plexus at the L4–L5 disc. This cadaveric study did not simulate lateral retractor placement in the psoas; however, the cadaveric lower extremity had been amputated mid-thigh.…”
Section: Discussionmentioning
confidence: 99%
“…These results show that when considering the trans-psoas and oblique approaches, sitting MRIs may dissuade surgeons from attempting an LLIF in specific patients. Flexion of the hips to 45–60 degrees intraoperatively has been advocated by O'Brien et al [ 16 ] in which they reported it would reduce strain in the lumbar plexus at the L4–L5 disc. This cadaveric study did not simulate lateral retractor placement in the psoas; however, the cadaveric lower extremity had been amputated mid-thigh.…”
Section: Discussionmentioning
confidence: 99%
“…Another documented risk in minimally invasive lateral approach was damage to the genitofemoral nerve [ 20 ]. A precise knowledge of the position of the genitofemoral nerve and performing an appropriate retraction might be critical to reduce this complication [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lumbar plexus safety remained a concern. However, prone positioning with the hips neutral to extended seems to lengthen the psoas muscle and draw it and the plexus with it more posteriorly [ 13 , 14 ]. This, combined with a mid-disc initial docking and customized A-P exposure from there, have increased the authors’ comfort with access at L4–5.…”
Section: Methodsmentioning
confidence: 99%